ENTREPRENEURSHIP BAGI UMMAT ISLAM - Retnanto, Agus (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
Learning social sciences, including about economics should be necessary to study the most fundamental ideas that gave birth to the science and economic system. If we examine more deeply about economic policy built on the idea of capitalist economic system, then we can know the depravity of the system and contradiction with Islam. We can see clearly the thoughts of Islamic economics. Islamic economic thought that this could provide a solution to the problems existing economic life with appropriate solutions and make a distinctive life style, as opposed to capitalist life, both related to the subjects and aspects details.According to Islamic law, the vision, mission, and goals of the business management should explain the orientation of Islamic law. His vision is to make the business as a vehicle for business managers to achieve profits shaded pleasure of God. Mission and goals that integration is not to realize the existence of the Human Resources professional who has the maturity of personality (syakhsiyyah) Islam, through the mindset and attitude of Islamic patterns. Maturity will be reflected in the business orientation and activity of every Muslim Human Resources. On the basis of the law anyway, strategic step for every Muslim activities of the Human Resources is the law itself. It is as a rule of usul, which states,